A survey of the paleontological heritage of Paraná State, Brazil - Christopher Santos; Antonio Liccardo (Journal of the Geological Survey of Brazil, 2021)
The state of Paraná has a considerable area with sedimentary outcrop rocks from the Paraná Sedimentary Basins (Paleozoic and Mesozoic) and Bauru (Mesozoic), Curitiba Basin (Cenozoic), and metasedimentary basement rocks (Proterozoic) with fossiliferous content. The state’s paleofauna and paleoflora, geologically distributed over more than one billion years, are diversified and acknowledged in several scientific publications. On this regard, a survey of the main collections and paleontological sites in Paraná state (Table 1) was conducted to provide a basis for the conception of a geoscience museum and with the scope of presenting representative fossils of the geological history of this region.  The methodological procedures consisted of literature search, consultations with paleontologists, visits to various state institutions and a selection of the samples in different sectors of the State University of Ponta Grossa (UEPG). The surveyed set of paleontological collections and sites indicate the heritage that is known by the state research institutions and museums and allowed to organize and quantify the set of fossils that comprise the collection of the UEPG’s Museum of Natural Sciences, which now exhibits to the public the evolutionary history of Paraná’s fossils. The survey identified 25 geosites in the state and 10 museological institutions located in 20 municipalities, which represent the most valuable scientific and educational paleontological heritage, as emphasized in this text.